Teste de tetrazólio para avaliação da qualidade de sementes de quiabo - Souza, Antonia Adailha Torres (Universidade Federal Rural do Semi-Árido, 2016)
The objective of this work was to study the tetrazolium test efficiency to verify the viability of okra seeds. The first experiment tested whether pre-conditioning and preparation methods. To overcome cutaneous hardness, we evaluated three methods to the best way of preconditioning: sulfuric acid (96%) for 1, 3 and 6 minutes; warm water (60 ° C) for 3, 6 and 10 minutes and ethyl alcohol ( 98%) for 30, 60 and 90 minutes. Four replications of 25 seeds were used, then the seeds were immersed in water at 25 ° C for 18 hours and then exposed to tetrazolium solution (with or without cut) at concentrations of 0.025 to 0.1% for 30, 60, 90 and 120 minutes in a germination chamber. The seeds were classified in four classes: discolored seed, poor coloring, satisfactory and excessive. The second experiment was carried out based on the results of the previous experiment. For this, four lots of okra seeds were subjected to preconditioning soaking in alcohol for 60 minutes followed by 18 hours of direct immersion in water at 25 ° C. Then, the seeds were cut longitudinally, immersed in 0.025 solutions; 0.050 and 0.075% for 60, 90 and 120 minutes and maintained in a growth chamber at 35 and 40° C. After this period, the seeds were classified with basis on the color (bright red pink or strong red carmine). At the same time, the germination test was installed, and the results were used as reference to the tetrazolium test. The experiment was conducted in a completely randomized design, in a factorial 3 x 3 + 1, three concentrations of the tetrazolium salt, three periods of immersion and the witness. The average of viable seeds tetrazolium test were compared by Tukey test at 5% significance level. The comparison between the means of the tetrazolium test and the germination test was taken by Dunnett test at 5% significance level. For preconditioning phase, it is recommended soaking seeds in alcohol for 60 minutes followed by 18 hours of immersion in distilled water at 25 ° C. The completion of the facilitated penetration of the cutting tetrazolium solution. For staining, we must use the concentration of 0.025% in 90 minutes time. The tetrazolium test is effective to estimate the viability of okra seeds in tetrazolium solution of 0.075% for 90 minutes
Tetrazolium test methodology for assessment of okra seeds quality
Keywords: Quiabo; Testes rápidos; Tetrazólio; Okra; Rapid tests; Tetrazolium; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA